The Hybrid Face Paradoxes of the Visage in the Digital Era - Leone, Massimo (Routledge/FACETS Advances in Face Studies, 2024)
This original and interdisciplinary volume explores the contemporary semiotic dimensions of the face from both scientific and sociocultural perspectives, putting forward several traditions, aspects, and signs of the human utopia of creating a hybrid face. The book semiotically delves into the multifaceted realm of the digital face, exploring its biological and social functions, the concept of masks, the impact of COVID-19, AI systems, digital portraiture, symbolic faces in films, viral communication, alien depictions, personhood in video games, online intimacy, and digital memorials. The human face is increasingly living a life that is not only that of the biological body but also that of its digital avatar, spread through a myriad of new channels and transformable through filters, post-productions, digital cosmetics, all the way to the creation of deepfakes. The digital face expresses new and largely unknown meanings, which this book explores and analyzes through an interdisciplinary but systematic approach. The volume will interest researchers, scholars, and advanced students who are interested in digital humanities, communication studies, semiotics, visual studies, visual anthropology, cultural studies, and, broadly speaking, innovative approaches about the meaning of the face in present-day digital societies.